2014
DOI: 10.1002/col.21921
|View full text |Cite
|
Sign up to set email alerts
|

Optimum solution of the CIECAM02 yellow–blue and purple problems

Abstract: Brill [Color Res Appl 2006;31:142-145] and Brill and S€ usstrunk [Color Res Appl 2008;33:424-426] found that CIECAM02 has the yellow-blue and purple problems and gave partial solutions to them. In this article we model the optimum solution to the yellow-blue and purple problems simultaneously as a constrained non-linear optimization problem. An optimum solution resulting in a new CAT02 matrix is numerically obtained. This new matrix satisfies the nesting rule and performs better than the Hunt-Pointer-Est ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…We already know that the source of the problem in the CIECAM02 model is the original CAT02 matrix M02 which does not satisfy the nesting rule, while the matrices MHPE and MOPT solve the problem and satisfy this rule: it is important that the matrix M16 should also satisfy the nesting rule. The structure of the CAM16 model is different from that of the original CIECAM02 model, and, under the new structure, the nesting rule is defined by Equation with the matrix M set equal to the matrix M16.…”
Section: Performance Of the Cat16 Transform The Cam16 Model And Thementioning
confidence: 99%
See 4 more Smart Citations
“…We already know that the source of the problem in the CIECAM02 model is the original CAT02 matrix M02 which does not satisfy the nesting rule, while the matrices MHPE and MOPT solve the problem and satisfy this rule: it is important that the matrix M16 should also satisfy the nesting rule. The structure of the CAM16 model is different from that of the original CIECAM02 model, and, under the new structure, the nesting rule is defined by Equation with the matrix M set equal to the matrix M16.…”
Section: Performance Of the Cat16 Transform The Cam16 Model And Thementioning
confidence: 99%
“…Brill and Süsstrunk also found that the CIECAM02 model exhibited the so‐called “yellow‐blue problem” and the “purple problem,” and they devised a rule for correcting them, which they called the nesting rule. If we let ΩM be the chromaticity domain of all X , Y , and Z values giving non‐negative R, G, and B response signals with the transformation defined by the matrix boldM (see Equation ), and similarly for ΩHPE, then the nesting rule can be exactly stated as: ΩCIEΩMΩHPE. …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations